PANDANGAN HUKUM ISLAM TERHADAP ADAT TOPO SALIA DI DESA MANINILI BARAT KECAMATAN TINOMBO SELATAN KABUPATEN PARIGI MOUTONG - Nizrah Nizrah; Nasaruddin Nasaruddin; Hamiyuddin Hamiyuddin (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2020)
This research has a problem that how is the implementation of the topo salia custom in Desa Maninili Barat, Kecamatan Tinombo Selatan, Kabupaten Parigi Moutong, and what is the view of Islamic law on the topo salia custom. The research method used is a qualitative method that describes field research. In the data collection technique, the writer used the method of observation and direct interviews with informants, namely the village head and several religious figures as well as documentation. Then, the results of the research found that first the topo salia custom is a ritual that is carried out in the month of Rabiul Awal to commemorate the birthday of the Prophet Muhammad. namely on the 12th of Rabiul Awal, this tradition was carried out with the aim of rejecting calamities and making their children live and cultured. Second, according to the view of traditional Islamic law, topo salia does not contradict Islamic law because it contains Islamic values, such as deliberation, mutual cooperation, strengthening friendship, and a form of gratitude to Allah swt.